Pemahaman Manajemen Dakwah dalam Organisasi Politik dalam Partai Keadilan Sosial (PKS) Sejarah, Tantangan, Strategi dan Dampaknya Terhadap Masyarakat - Wiratama, Muhammad Ikrar; Fauziah, Nabila; Abdurrahman, Ishak; Mutoharoh, Siti (Universitas Pahlawan Tuanku Tambusai, 2025)
This article discusses the management of dakwah in political organizations, focusing on the concept, challenges, opportunities, and its impact on society. Through an analytical approach, this study identifies the role of political organizations in spreading dakwah values ​​and the strategies used to manage dakwah effectively. The results of the study indicate that good dakwah management can improve social justice and public morality, although it also has the potential to cause polarization. This study is expected to contribute to the development of da'wah theory and practice in a political context.